2005
DOI: 10.1093/nar/gki632
|View full text |Cite
|
Sign up to set email alerts
|

Covalent ligation studies on the human telomere quadruplex

Abstract: Recent X-ray crystallographic studies on the human telomere sequence d[AGGG(TTAGGG)3] revealed a unimolecular, parallel quadruplex structure in the presence of potassium ions, while earlier NMR results in the presence of sodium ions indicated a unimolecular, antiparallel quadruplex. In an effort to identify and isolate the parallel form in solution, we have successfully ligated into circular products the single-stranded human telomere and several modified human telomere sequences in potassium-containing soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 47 publications
(42 reference statements)
2
61
0
3
Order By: Relevance
“…It is now well established that G-rich DNA can form a wide range of structures, depending on the sequence and conditions (10,19,33,34). Our single-molecule investigation of G-quadruplexes derived from human telomeric DNA detected six distinct conformational states, which differ in static spectroscopic signals and͞or in their dynamic characteristics.…”
Section: Discussionmentioning
confidence: 83%
“…It is now well established that G-rich DNA can form a wide range of structures, depending on the sequence and conditions (10,19,33,34). Our single-molecule investigation of G-quadruplexes derived from human telomeric DNA detected six distinct conformational states, which differ in static spectroscopic signals and͞or in their dynamic characteristics.…”
Section: Discussionmentioning
confidence: 83%
“…Structure polymorphism of the human telomeric G-quadruplexes, particularly for the 22-nt wtTel22 sequence, has been reported by various methods. The different CD spectra have been observed for human telomeric sequences in Na + and K + solution [32,37,39,40]. Multiple structures formed by wtTel22 in Na + and K + solution have also been reported in a 125 I-radioprobing study [36], a FRET study [33], a platinum cross-linking study [34], a chemical ligation study [40], and a photon correlation spectroscopic study [39].…”
Section: Review Of Multiple Biophysical Studiesmentioning
confidence: 98%
“…A large number of biophysical and crosslinking studies have been reported on the K + -structure of human telomeric G-quadruplexes [32][33][34][36][37][38][39][40]. Structure polymorphism of the human telomeric G-quadruplexes, particularly for the 22-nt wtTel22 sequence, has been reported by various methods.…”
Section: Review Of Multiple Biophysical Studiesmentioning
confidence: 99%
See 2 more Smart Citations